Growth response to pre-commercial thinning of lodgepole pine is short-term but the effects on size distribution persist for decades - Shes K. Bhandari; Bradley D. Pinno; Kenneth J. Stadt; Barb R. Thomas (The Forestry Chronicle)
Pre-commercial thinning in Alberta is a potential option for increasing the growth rate and shortening the rotation age of regenerating forests. Previous studies have focused on the evaluation of either the immediate- or long-term response to thinning after many decades. Our current study compares the pre-commercial thinning response in lodgepole pine for a 10-year period immediately after thinning, and again 38-45 years after thinning, based on 22 paired plots of precommercially thinned trials in Alberta. The first group of plots was pre-commercially thinned in 1984, measured in 1985 and 1995 (short-term) and the second group was pre-commercially thinned between 1962 and 1969 and measured in 2007 and 2017 (long-term). In the short-term, individual tree DBH growth was 56% greater in pre-commercially thinned plots, while in the long-term plots, there were no measured growth differences between pre-commercially thinned and unthinned plots. Small- and medium-sized trees benefited more from pre-commercial thinning than larger trees. However, at the stand level, the number and volume of merchantable-sized trees (≥13.5 cm DBH) were higher in pre-commercially thinned plots than in unthinned plots in both the short- and long-term. Although the growth response of thinning appeared to be a short-term response (number and volume of larger trees), yield at the end of the long-term measurement period was still higher in pre-commercially thinned than in unthinned plots.